Natural occurrence of Azospirillum brasilense in petunia with capacity to improve plant growth and flowering - Toffoli, Lucia Mercedes (2021)
To evaluate the natural occurrence of the plant growth-promoting bacterium Azospirillum brasilense and petunia plants, local strains were isolated and characterized by biochemical and molecular methods. Three strains were assessed in greenhouse conditions using Petunia × hybrida Ultra™. Treatments: Plants without bacterial inoculation or chemical fertilization; fertilized with NPK and KNO3; and independently inoculated with the strains 2A1, 2A2, and 2E1 by submerging their roots in a bacterial suspension (~106 CFU·ml−1). Root length, dry weight of roots and shoots, leaf area, leaf greenness, and nutrient content were evaluated. The number of days from transplanting to the opening of the first flower and the number of flowers per plant were also determined. As a result, five isolates were characterized as A. brasilense, showing the capacity to produce indoles and siderophores, to solubilize phosphate, nitrogenase activity, and nifH-PCR amplification. In general, all the parameters of the plant assay were improved in plants inoculated with A. brasilense, with variations among the strains, as well as the onset of flowering and the number of flowers per plant, compared with uninoculated or fertilized plants. This is the first report on the natural occurrence of A. brasilense in petunia with the capacity to improve plant growth and flowering.